Cross-cultural Adaptation and Psychometric Properties of Nepali Version of Developmental Coordination Disorder Questionnaire - Shrestha, N; Thapa, A; Gupta, S; Lepcha, L; Adhikari, SP (Kathmandu University Medical Journal, 2023)
Background Revised developmental coordination disorder questionnaire (DCDQ’07) is the best available population-based screening tool to identify developmental coordination disorder and being a parent reported tool, it needs to be available in Nepali language for its application in Nepali population. Objective The objective of this study was to cross-culturally adapt developmental coordination disorder questionnaire into Nepali (DCDQ-NP). The psychometric properties of Nepali version of Developmental coordination disorder questionnaire were established. Method The adaptation was done following Beaton’s guideline and the psychometric properties was studied in the community sample of 165 parents of school going children of 5-15 years. Fifty parents were asked to refill the questionnaire after the two weeks period. The study determines internal consistency, test retest reliability, floor and ceiling effect and construct validity. Result Significant cultural adaptation was required to obtain relevant Nepali version. The Nepali version of Developmental coordination disorder questionnaire demonstrates high internal consistency (α = 0.912), excellent test-retest reliability (IC = 0.901) and the floor and ceiling effect were acceptable. Principal component analysis showed three factor structure accounting 62% of variance. Conclusion The developmental coordination disorder questionnaire into Nepali were successfully translated and culturally adapted preserving its original concept. It showed good psychometric properties in a Nepali population. The adapted questionnaire shall be of significance in carry out further research in developmental coordination disorder in Nepal.